2013 8th International Symposium on Image and Signal Processing and Analysis (ISPA) 2013
DOI: 10.1109/ispa.2013.6703839
|View full text |Cite
|
Sign up to set email alerts
|

A multichannel and multiple position adaptive room response equalizer in warped domain

Abstract: An adaptive multichannel and multiple position room response equalization system is proposed. The room responses are adaptively estimated with good accuracy by reducing the interchannel coherence with a technique based on the missing fundamental phenomenon, that introduces only a mild alteration of the sound timbre. The equalizer is designed in warp frequency domain for improving equalization in the low frequency region, reducing the computational cost of the design and deriving an algorithm capable to work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 15 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…Despite these limitations, deconvolution with regularization approaches has been successfully applied in combination with other techniques used to avoid perceivable distortions. For example, it has been combined with frequency warping [83,84], or used in wave field synthesis [85].…”
Section: Frequency Domain Deconvolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these limitations, deconvolution with regularization approaches has been successfully applied in combination with other techniques used to avoid perceivable distortions. For example, it has been combined with frequency warping [83,84], or used in wave field synthesis [85].…”
Section: Frequency Domain Deconvolutionmentioning
confidence: 99%
“…The obtained results have shown that the performance of this rather simple structure can be improved by considering a multi-point solution, which results in an increased width of the equalized zone. In [84], the approach of [180] was further elaborated considering frequency warping in the low-frequency region to improve perception. Specifically, the room responses at different positions in the zone to be equalized are estimated in the warped domain and the common trend of these responses is extracted as a prototype function.…”
Section: Frequency Domain Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Different subjective evaluation for inverse filtering of linear systems can be found in [27] This chapter presents different schemes to solve the room equalization problem. First and as the underlying structure, the single channel adaptive filtering algorithm introduced in Section 2.3 for room equalization applications is studied in this chapter.…”
Section: Subjective Evaluationmentioning
confidence: 99%